Automatic control system of highway lights - Yasir Hashim; Mohammed Nazmus Shakib (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This research provides new effective and cheap designed system for save electrical energy dissipation in all urban area roads and highways. The aim of this system is to minimizing the waste electrical power on highways and urban  area roads. The designed system depends on two Arduino circuit types, master and slave. The master  Arduino has an ability to detect the day light by light dependent resistor (LDR) sensor and cars movements by pyroelectric infrared (PIR) sensor, according to these conditions, the master will send a signal by XBee module works as transmitter to the following five slaves  Arduino which are waiting for a signal and receive it by XBee module works as receiver to turn ON the lights for 5 minutes then OFF it if there is no car movement on the street. The system can mount directly to the highway lights. The system has been tested and applied on the street lights, the system works perfectly and slaves respond fastly and effectively to the master Arduino signal.